2022
DOI: 10.1113/jp281930
|View full text |Cite
|
Sign up to set email alerts
|

Insights on gastrointestinal motility through the use of optogenetic sensors and actuators

Abstract: support-information-section).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 197 publications
0
3
0
Order By: Relevance
“…These findings, together with our study, suggest that miR‐10b deficiency leads to intestinal permeability, dysregulation of tight junctions, and gut immune dysfunction. Additionally, it is of paramount importance to uncover the role of miR‐10b‐5p in other cells essential to proper gut function and maintenance, such as neurons, PDGFRα cells, smooth muscle cells, etc 55–60 . Furthermore, the leaky gut phenotype should be assessed using an Ussing chamber, which is currently the gold standard for measuring epithelial barrier permeability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings, together with our study, suggest that miR‐10b deficiency leads to intestinal permeability, dysregulation of tight junctions, and gut immune dysfunction. Additionally, it is of paramount importance to uncover the role of miR‐10b‐5p in other cells essential to proper gut function and maintenance, such as neurons, PDGFRα cells, smooth muscle cells, etc 55–60 . Furthermore, the leaky gut phenotype should be assessed using an Ussing chamber, which is currently the gold standard for measuring epithelial barrier permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is of paramount importance to uncover the role of miR‐10b‐5p in other cells essential to proper gut function and maintenance, such as neurons, PDGFRα cells, smooth muscle cells, etc. 55 , 56 , 57 , 58 , 59 , 60 Furthermore, the leaky gut phenotype should be assessed using an Ussing chamber, which is currently the gold standard for measuring epithelial barrier permeability. Moreover, the validation of the leaky gut phenotype should be conducted using a larger number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…ICC are rich in multiple organelles, including numerous mitochondria and abundant endoplasmic reticula (41). With a highly branched morphology and cellular network, ICC are an important component of the gastrointestinal tract (42). Additional evidence has shown that ICC contribute to intestinal motility by generating spontaneous electrical depolarization and increasing smooth muscle excitability (43).…”
Section: Discussionmentioning
confidence: 99%